Syi’ah dan Perubahan Sosial - Adi Cilik Pierewan * (Pendidikan Sosiologi FIS UNY, 2007)
The aim of this article is to describe about Syi’ah in Indonesia. This article will describe about the first history of Syi’ah entered to Indonesia. Second is social background that effected development of Syi’ah in Indonesia. Third is the factors that push of founding of IJABI and fourth is purposes of IJABI. Syi’ah, the marginal school in Islamic tradition, is the interesting topic that can be explored in social change discipline. In the early development of Islam, Syi’ah is the form of rebellion that attack to Islamic mainstream tradition. Islamic mainstream tradition here, s represented by Sunni that dominate Islamic kingdom. Keywords: Social change; syi’ah; Islamic tradition